2020
DOI: 10.1007/s12031-020-01595-8
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Biallelic NSUN3 Variants Cause Early-Onset Mitochondrial Encephalomyopathy and Seizures

Abstract: Epitranscriptomic systems enable post-transcriptional modifications of cellular RNA that are essential for regulating gene expression. Of the~170 known RNA chemical modifications, methylation is among the most common. Loss of function mutations in NSUN3, encoding the 5-methylcytosine (m5C) methyltransferase NSun3, have been linked to multisystem mitochondrial disease associated with combined oxidative phosphorylation deficiency. Here, we report a patient with early-onset mitochondrial encephalomyopathy and sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 11 publications
0
22
1
Order By: Relevance
“…Thus, f 5 C formation is disturbed by mutations in either ALKBH1 or NSUN3. Patients with NSUN3 mutations show a combined developmental disability and microcephaly [28,29]. These symptoms were not completely consistent with the phenotype observed in our established Alkbh1 KO mice.…”
Section: Discussioncontrasting
confidence: 50%
“…Thus, f 5 C formation is disturbed by mutations in either ALKBH1 or NSUN3. Patients with NSUN3 mutations show a combined developmental disability and microcephaly [28,29]. These symptoms were not completely consistent with the phenotype observed in our established Alkbh1 KO mice.…”
Section: Discussioncontrasting
confidence: 50%
“…The reason may be that advanced tumors require a lot of energy and tumor cells improve their mitochondrial activity and obtain more energy by self-upregulating NSUN4 and other genes. NSUN3 was a putative methyltransferase in mitochondria [28], whose aberration may lead to a variety of diseases [29,30]. Many studies have reported that TET2 can inhibit tumors, and its mutation can induce the occurrence and development of tumors [31][32][33][34].…”
mentioning
confidence: 99%
“…Diseases related to energy metabolism disorder are also associated with the mitochondrial RNA m 5 C modification. For example, NSUN3 may be associated with multisystem mitochondrial disease associated with a combined oxidative phosphorylation deficiency 108 . In leukemia cells, NSUN3/DNMT2 and NSUN1 regulate the formation of 5-azacitidine-sensitive chromatin structures in an antagonistic manners 25 .…”
Section: Biological Function Of M 5 C In Eukaryote and Diseasementioning
confidence: 99%